Use of Various concentrations of plant growth regulator (PGR) of Sweet Corn on the Growth and Production of sweet potato (Ipomoea batatas L.) - Upe, Ambo (International Journal of Environment, Agriculture and Biotechnology, 2019)
The use of Plant Growth Regulating can be sourced from synthetic products and products made from natural or organic ingredients. This study aims to determine the effect of the use of various plant growth regulating (PGR) concentrations of sweet corn on the growth and production of Sweet Potatoes. The study was conducted in Wiringpalennae Sub-District, Tempe Subdistrict, Wajo Regency, South Sulawesi Province, Indonesia 2018. The method used was Randomized Block Design (RBD), consisting of four (4) treatments, namely without PGR (z0), PGR 3 ml / l water (z1), PGR 5 ml / l water (z2), and PGR 7 ml / l water (z3). Each treatment was repeated three times so that the number of treatment combinations was 12 combinations. The results of the study indicate that the administration of 7 ml / l of water in sweet potato produced an average production of fresh tuber 60.51 t ha-1.